Cover Picture: Photochemical Electrocyclization of Poly(phenylacetylene)s: Unwinding Helices to Elucidate their 3D Structure in Solution (Angew. Chem. Int. Ed. 15/2021). Issue 15 (1st March 2021) - Rey‐Tarrío, Francisco; Rodríguez, Rafael; Quiñoá, Emilio; Riguera, Ricardo; Freire, Félix
Abstract : Light irradiation was used as a structural tool to elucidate the three‐dimensional  framework of helical polymers via photochemical electrocyclization of their polyene backbones. Details of this study are reported by Félix Freire et al. in their Research Article on page 8095 .